Everyman - Roth, Philip; Guidall, George (Prince Frederick, MD : Recorded Books, 2006)
The hero of Everyman is obsessed with mortality. As he reminds himself at one point, "I'm thirty-four! Worry about oblivion when you're seventy-five." But he cannot help himself. He is the ex-husband in three marriages gone wrong. He is the father of two sons who detest him, despite a daughter who adores him. And as his health worsens, he is the envious brother of a much fitter man.
Compact disc.
Narrated by George Guidall.
Keywords: Aging -- Fiction; Death -- Fiction; Older people -- Fiction; Audiobooks; Psychological fiction